Pengaruh Kepuasan Kerja Dan Budaya Organisasi Terhadap Organizational Citizenship Behavior (OCB) di PT Pupuk Sriwidjaja Palembang (Kasus di Divisi Teknologi) - Bharata .; Zunaidah .; Yuliansyah M. Diah (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
This study aimed to determine the effect of job satisfaction and organizational culture on Organizational Citizenship Behavior (OCB) of the employees in PT Pupuk Sriwidjaja Palembang  and it takes the case in Division of Technology. Luthans stated that there are several dimensions determining job satisfaction, those are job itself, salary, supevision, co-workers, and working conditions. Meanwhile, according to Robbin, there are seven characteristics of organizational culture, those are innovation and risk taking, attention to detail, outcome orientation, team orientation, aggresiveness and stability.  The determination of number of respondents in this study uses a stratified random sampling method in Technical Inspection Department, Production Planning and Controling Department, Safety and Environment Department and Laboratory Department. The calculation of the sample size is based on Slovin formula and it gets a total sample of 66 employees.  The result of this study shows that job satisfaction do not have a significant effect on OCB.  While organizational culture significantly has positive effect on OCB. Job satisfaction and organizational culture simultantly has effect on OCB with organizational culture is the dominant variable.